SUITABILITY OF INSTRUCTIONAL OBJECTIVES WITH A PAPER AND PENCIL TEST THAT DEVELOP BY CERTIFIED BIOLOGY TEACHERÂ IN THE BOJONEGORO DISTRICT - RETNOSARI, NILAM (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
This study aims to describe the suitability of the instructional objectives with paper and pencil test, developed by certified biologist teachers in the Bojonogoro district. The method used in this research is survey. Population and sample are 26 certified biology teacher. Documentation data retrieval techniques. The data obtained and analyzed descriptively. The results showed that 43.06% items according to the taxonomic level learning objectives are developed, 39.35% items are not in accordance with the taxonomy of learning objectives and the level of 17.59% of the items were not developed learning goals. Keywords: Instructional Learning Objective, Paper and Pencil Test, Biology Teachers, Certification, Bojonegoro.